The Role of Primary School Teachers on Online Learning with WhatsApp Group - Agus Satriyo Pamungkas; Septi Budi Sartika (Jurnal Ilmiah Sekolah Dasar, 2021)
The conditions of the Covid-19 pandemic require learning to continue even without face to face, one of which is learning through online learning with the WhatsApp Group application. This study aims to explore and describe the role of primary school teachers in teaching and learning from home through the WhatsApp Group. The focus of this research leads to the pedagogical competence of teachers in classroom management which consists of planning, implementing, and assessing learning. This research uses qualitative research with the type of phenomenology, which is to reveal the facts about teacher teaching and learning activities through the WhatsApp Group application. The data analysis technique uses the Miles & Hubberman model which includes data reduction, data presentation, verification, and conclusions. Checking the validity of the data using triangulation techniques, namely questionnaires, interviews, and documentation. The results show that of the 11 existing aspects, there is only one aspect that has not been achieved, namely conducting discussions through discussion forums that have not been achieved, while for other aspects such as providing modules, providing teaching materials, assigning assignments, assessing assignments, providing input and reviewing learning has been accomplished. Further research is expected to use the triangulation of resources, namely teachers, students, and student guardians because learning activities are carried out from home so that the analysis is more in-depth.